A conception of moral wayfinding for business managers: The obligation for a sustainable corporation. (15th February 2021) - Valentinov, Vladislav; Pérez-Valls, Miguel
Abstract: While corporate managers are under moral obligation to run their corporations in a sustainable way, the growing corporate sustainability challenges necessitate the growing complexity of decisions which need to be made by managers. To help managers to deal with these trends, the paper proposes a novel conception of "moral wayfinding", a term inspired by Chia's (2017) process-philosophic approach to organizational learning. Moral wayfinding relies on the immersive engagement of individual managers with their social environments in a way that infuses their mindsets with the moral commitment to the long-run sustainability of their corporations. In addition to process philosophy, the idea of moral wayfinding draws inspiration from systems theory, stakeholder theory, and business ethics in order to fill some of the gaps in the extant approaches to managerial guidance. Systems theory illuminates the complexity of sustainability issues but tends to miss the complexity of moral decision making; business ethics embraces the latter complexity but struggles to link it to the rational self-interest which is further reinforced by the Luhmannian systems-theoretic idea of complexity reduction. The process-philosophic idea of moral wayfinding integrates these literatures and thus supports the moral motivation of managers to pursue corporate sustainability.